The Theatre of Tennessee Williams - Murphy, Brenda (Bloomsbury Academic, 2014)
In Brenda Murphy's major study of his work she examines Williams' life and career and provides an analysis of more than a score of his key plays, including in-depth studies of major works such as A Streetcar Named Desire, The Glass Menagerie, Cat on a Hot Tin Roof and others. She traces the artist figure who features in many of Williams' plays to broaden the discussion beyond the normal reference points. Included are essays by Bruce McConachie, John S. Bak, Felicia Hardison Londré and Annette Saddik, showcasing different critical perspectives and approaches.